Bridging Gulfs in Life and Literature: Henry Green and the Process of “Going Over” (American & British Studies Annual, 2011)
Henry Green, a writer whose works were published between 1926 and 1952, has been traditionally regarded as standing between the two traditions that dominated in the literary landscape of the 1930s and 1940s in Britain, namely modernism and (new) realism. The debate on Green as either an experimental modernist or socially-engaged leftist realist has led to the production of an image of an artist (writer) whose position in the canon of British literature of this period is fascinating, yet highly problematic. Focusing on selected prose of Henry Green, namely Living (1929), Party Going (1939) and Pack My Bag: A Self-Portrait (1940), this paper discusses the ways the subject of an a writer is negotiated through on the one hand the subversion of established literary traditions, and on the other through the active engagement in the social problems performed in the act of “going over”.
Keywords: Henry Green; Living; Party Going; Pack My Bag: A Self-Portrait; modernism; realism; going over; artistic identity